Analysis of the take-off of top ski jumpers - Müller, S.; Kreibich, S.; Seidel, I. (Sciene and nordic skiing III, 2016)
In ski jumping the take-off plays a key role within the entire jump movement. The intensity of the take-off (vertical take-off velocity) determines the flight height and the angular momentum has a direct impact on the transformation into an effective flight position and on the flight distance. Due to the changes in the material - jump suits, bindings or shoes - but also due to the use of standardized track and ice-track systems the best athletes permanently move their centre of mass more forward in the inrun position and in take-off. This becomes apparent particularly in smaller lower body angles at the take-off edge. Long-term analyses of international competitions prove this development. For the take-off diagnostics is a special way with the installation of sensors in the take-off table. Thus, the applied forces can be determined during the jump motion (Dickwach & Wagner, 2004; Virmavirta & Komi, 1993a, 1993b). Large differences in the force-length-curves were found in analyzing the takeoff execution of German and international top athletes in addition to the differences in body angle. Differences exist in the force level, in the point of maximum force and in the general characteristics of the force-length-curve (Müller, Kreibich & Wiese, 2014). The research question of this study was if typical characteristics can be found and whether they are related to take-off types based on the kinematic parameters and the take-off velocity. Therefore the take-off execution in terms of the force development and force performance during the take-off phase of top athletes were analyzed.